2012
DOI: 10.3892/ol.2012.955
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclin E in stage III colorectal carcinoma

Abstract: Abstract. Carcinogenesis is characterized by an abnormal regulation of the cell cycle. Regulators of the cell cycle such as cyclin E play an important role in neoplasia and may be correlated with prognosis. The clinical significance of the expression of cyclin E in stage III colorectal carcinoma has not yet been investigated. The expression of cyclin E was evaluated in 49 patients. Using a multivariate analysis, the expression of cyclin E in the tumor at diagnosis was compared with various clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It leads to tumorigenesis likely due to genetic instability . In CRC, high expression of cyclin E1 in tumour increased the risk of tumour recurrence and was correlated with its malignancy, representing a possible prognostic marker …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It leads to tumorigenesis likely due to genetic instability . In CRC, high expression of cyclin E1 in tumour increased the risk of tumour recurrence and was correlated with its malignancy, representing a possible prognostic marker …”
Section: Discussionmentioning
confidence: 99%
“…63 In CRC, high expression of cyclin E1 in tumour increased the risk of tumour recurrence and was correlated with its malignancy, representing a possible prognostic marker. 64,65 Dot blot showed that METTL3 could increase m6A modification in CRC cells. MeRIP and dual-luciferase assays showed that METTL3 could specifically catalyse m6A sites of 3′-UTR in CCNE1 mRNA, which increased the stability of CCNE1 mRNAs and eventually lead to increased cyclin E1 expression.…”
Section: Discussionmentioning
confidence: 99%